Soft and Ion‐Conducting Materials in Bioelectronics: From Conducting Polymers to Hydrogels. Issue 5 (24th January 2020) - Jia, Manping; Rolandi, Marco
Abstract: Bioelectronics devices that directly interface with cells and tissue have applications in neural and cardiac stimulation and recording, electroceuticals, and brain machine interfaces for prostheses. The interface between bioelectronic devices and biological tissue is inherently challenging due to the mismatch in both mechanical properties (hard vs soft) and charge carriers (electrons vs ions). In addition to conventional metals and silicon, new materials have bridged this interface, including conducting polymers, carbon‐based nanomaterials, as well as ion‐conducting polymers and hydrogels. This review provides an update on advances in soft bioelectronic materials for current and future therapeutic applications. Specifically, this review focuses on soft materials that can conduct both electrons and ions, and also deliver drugs and small molecules. The future opportunities and emerging challenges in the field are also highlighted. Abstract : This review highlights soft and ion‐conducting materials in bioelectronic devices as a promising opportunity to bridge biological tissue and electronic devices. Focus is on the emerging challenges and future therapeutic applications.